Gut microbiota, circulating inflammatory proteins and sepsis: a bi-directional Mendelian randomization study - Li, Zuming; Lin, Liangcai; Kong, Yunqi; Feng, Jieni; Ren, Xiaolei; Wang, Yushi; Chen, Xueru; Wu, Siyi (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundGut microbiota is closely related to the occurrence and development of sepsis. However, the causal effects between the gut microbiota and sepsis, and whether circulating inflammatory proteins act as mediators, remain unclear.MethodsGut microbiota, circulating inflammatory proteins, and four sepsis-related outcomes were identified from large-scale genome wide association studies (GWAS) summary data. Inverse Variance Weighted (IVW) was the primary statistical method. Additionally, we investigated whether circulating inflammatory proteins play a mediating role in the pathway from gut microbiota to the four sepsis-related outcomes.ResultsThere were 14 positive and 15 negative causal effects between genetic liability in the gut microbiota and four sepsis-related outcomes. Additionally, eight positive and four negative causal effects were observed between circulating inflammatory proteins and the four sepsis-related outcomes. Circulating inflammatory proteins do not act as mediators.ConclusionsGut microbiota and circulating inflammatory proteins were causally associated with the four sepsis-related outcomes. However, circulating inflammatory proteins did not appear to mediate the pathway from gut microbiota to the four sepsis-related outcomes.